2002
DOI: 10.1038/sj.jhh.1001320
|View full text |Cite
|
Sign up to set email alerts
|

Is aldosterone the missing link in refractory hypertension?: aldosterone-to-renin ratio as a marker of inappropriate aldosterone activity

Abstract: Use of the random aldosterone-to-renin ratio (ARR) as a reliable marker of inappropriate aldosterone activity has led to primary aldosteronism (PA) being increasingly diagnosed in hypertensive patients. At least 10% of hypertensives have been found to have PA, the majority of whom presumably have bilateral adrenal hyperplasia or idiopathic hyperaldosteronism as an aetiology for PA. Whilst these patients clearly have excess aldosterone activity, they have in common many features that are found in hypertensive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 59 publications
1
21
1
Order By: Relevance
“…[28][29][30] Indeed, our study shows adrenal gland hypertrophy and an increase of the aldosterone:renin ratio, 13,14 suggesting that sympathetic activation may be involved in the postnephrectomy hypertrophy of the heart and remnant kidney. Although an activation of the renin-aldosterone system has been shown in patients with chronic kidney disease, 8,31 adrenal hypertrophy has been described only in animal studies.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…[28][29][30] Indeed, our study shows adrenal gland hypertrophy and an increase of the aldosterone:renin ratio, 13,14 suggesting that sympathetic activation may be involved in the postnephrectomy hypertrophy of the heart and remnant kidney. Although an activation of the renin-aldosterone system has been shown in patients with chronic kidney disease, 8,31 adrenal hypertrophy has been described only in animal studies.…”
Section: Discussionsupporting
confidence: 48%
“…Blood samples were collected to measure the following parameters: serum creatinine for estimating clearance (Cockcroft-Gault) and estimated GFR (Chronic Kidney Disease Epidemiology Collaboration [2009] creatinine equation) 12 ; aldosterone and renin after 30 minutes of rest and the aldosterone:renin ratio for the assessment of the renin-angiotensin-aldosterone system 13,14 ; procollagen type III as an indicator for cardiac fibrosis 15 and N-terminal probrain natriuretic peptide. Urinary protein concentration in midstream urine samples was divided by urinary creatinine concentration to estimate daily excretion of protein.…”
Section: Laboratory Analysismentioning
confidence: 99%
“…Strikingly, among patients that are resistant to combination antihypertensive therapy, the prevalence of PA is estimated to be Ϸ20% worldwide (3,6,7). The incidence of PA increases with the severity of hypertension, and among resistant hypertensives, mineralocorticoid receptor blockade is of broad benefit (8)(9)(10).…”
mentioning
confidence: 99%
“…[27][28][29][30] It is important to note that most patients with PA are normokalemic and would not be diagnosed if the screening required the presence of hypokalemia. Recent studies have demonstrated that fewer than 20% of PA patients are hypokalemic.…”
Section: Discussionmentioning
confidence: 99%